2013
DOI: 10.2174/0929867311320250008
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Based Antimicrobial Protease Inhibitors

Abstract: Limitations associated with the production cost, metabolic instability, side-effects, resistance and poor pharmacokinetics of organic protease inhibitors (PIs), which form an essential component of the front line HAART treatment for HIV, have fuelled efforts into finding novel, transition metal-based alternatives. Some of the attractive features of metalbased therapeutics include synthetic simplicity, solubility control, redox capability, expansion of coordination number and topography matching of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Metal-free phendione exerts its antimicrobial effect in several ways, such as disturbing the microorganism's crucial metal metabolism as well as interfering in its metal ion acquisition and its bioavailability for essential reactions (e.g., inhibiting the activity of metalloproteins), affecting the microbial cell homeostasis and culminating in the blockage of primordial biological events (e.g., nutrition, proliferation, differentiation, adhesion, invasion, dissemination and infection) (Santos et al, 2012 ). Protease inhibition is also a prime cellular target of this class of ligand and its associated metal complexes (Kellett et al, 2013 ). In this context, the aim of the present work was to investigate the effect of phendione and its Ag + and Cu 2+ complexes on P. verrucosa proliferation, ultrastructure, metallopeptidase activity, sterol content and morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-free phendione exerts its antimicrobial effect in several ways, such as disturbing the microorganism's crucial metal metabolism as well as interfering in its metal ion acquisition and its bioavailability for essential reactions (e.g., inhibiting the activity of metalloproteins), affecting the microbial cell homeostasis and culminating in the blockage of primordial biological events (e.g., nutrition, proliferation, differentiation, adhesion, invasion, dissemination and infection) (Santos et al, 2012 ). Protease inhibition is also a prime cellular target of this class of ligand and its associated metal complexes (Kellett et al, 2013 ). In this context, the aim of the present work was to investigate the effect of phendione and its Ag + and Cu 2+ complexes on P. verrucosa proliferation, ultrastructure, metallopeptidase activity, sterol content and morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of enzymatic hydrolysis was confirmed with the high blockage of activity (~90%) by pepstatin A (10 μM), a comercial aspartic peptidase inhibitor, as we previously showed in Palmeira et al [ 15 ]. Kellett et al [ 76 ] discussed the ability of some metallic compounds (metallocarborane, polyoxometalate and copper) acting as protease inhibitors, and their potential use as alternative drugs to organic protease inhibitors currently employed against protease-associated diseases. This review showed that metal-based agents have proteolytic enzymes as targets, are able to bind them and inhibit the wild-type HIV aspartic protease as well as parasitic proteases.…”
Section: Resultsmentioning
confidence: 99%
“…They form a variety of compounds with interesting spectroscopic and magnetic properties whose practical applications are the subject of ongoing research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In the cell, metals are usually found in their complexed form, either as standalone ions or inside specific planar carrier compounds encapsulated by proteins -e.g.…”
Section: Metal Ions In Natural Biological Systemsmentioning
confidence: 99%